Analisis Yuridis terhadap Perlindungan Hukum bagi Pemegang Obligasi tanpa Jaminan dalam Kepailitan Emiten di Pasar Modal - Gibran Ibnu Sina; Yahya Ayyash Ibrahim Pasha; Barbie Puteri (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
Economic development in today's world has grown rapidly, leading to numerous changes in human life. By investing in the capital market, it becomes one of the alternatives for financing the community's economy and is easily accessible to the public. One of them is to invest in bond securities in issuer companies. However, by purchasing bonds in the capital market with the issuer company, in addition to providing benefits through interest rates, there are risks, including if the issuer company goes bankrupt. Under these conditions, the holder of the unsecured bond will be positioned as a concurrent creditor, whose repayment is made after the separatist and preferred creditor. Although not guaranteed collateral, bondholders still obtain legal guarantees of their rights through information disclosure, the role of trustees, and arrangements within the applicable legal framework.